Capitals in artisanal and small-scale mining in Marmato, Colombia: Using the sustainable livelihoods framework to inform formalization. (December 2022) - Delgado Jiménez, Alejandro; Smith, Nicole M.; Holley, Elizabeth A.
Highlights: The sustainable livelihoods framework is useful for mapping and informing the potential of ASM to exist as a more sustainable livelihood for rural communities. Livelihood assets and different forms of capital available to artisanal and small-scale miners are combined and mobilized strategically to get their livelihood. Using a bottom-up approach and the sustainable livelihoods framework, reveals critical elements of ASM livelihoods and can be used to inform policy and development interventions. Identifying and analyzing several forms of capitals, their interactions, and their implications can provide insights for development and formalization interventions in contexts where ASM occurs. Abstract: This paper applies the concept of capitals in the sustainable livelihoods framework (SLF) to examine artisanal and small-scale mining livelihoods in the municipality of Marmato, Colombia and discusses the relevance of these findings to formalization efforts. Artisanal and small-scale mining (ASM) is an important and often traditional livelihood in the rural global south where income generating alternatives are scarce. Marmato is one of South America's oldest gold mining sites, and ASM has been intermittently practiced there since about 500 B.C. The present study maps ASM onto the five capitals of the SLF and identifies several forms of capitals that miners cited as the most relevant for pursuing ASM activities. The results show that artisanal and small-scale gold miners in Marmato strategically combine different forms of capital that enable them to make a living from mining; however, there are key factors that may impact the longer-term viability of artisanal and small-scale mining livelihoods. Although human, social, and financial capital function to support ASM livelihoods, the finite nature of natural capital and deterioration of physical capital erode the potential for sustainability of those livelihoods. This research highlights the utility of closely examining the capitals in the SLF and suggests that a more comprehensive understanding of ASM capitals can better inform formalization policies and associated development interventions.